Pilot Implementation of Statistical Models for Estimation of the Value-Added of Bulgarian Schools Using National Student Assessment Data - Danchev, Plamen; Bankov, Kiril; Stoimenova, Vessela; Atanassov, Dimitar (World Bank, Washington, DC, 2016)
The objective of this report is to describe the process and summarize the results from the pilot implementation of statistical models for measuring the value-added of Bulgarian schools through analysis of the national student’ assessments results. This report presents the technical aspects of the pilot and the key outcomes in terms of value-added measure for each of the schools included in the analysis. The report documents all data processing, adjustments, and procedures run as part of the school value added modeling and in this respect, it is also intended expert statisticians and researchers. The national student assessment results in Bulgaria are reported on a non-transformed raw point scale accompanied by a table that allows a transformation of the raw points to the six-grade rating scale, adopted for measuring students’ performance. Based on this, each school receives an average score and some means of comparison with other schools in the country. Analyzing the test results through value-added analysis is a new approach for the country and the findings from this pilot are intended to inform policy makers in Bulgaria about the advantages and limitations of value-added measures (VAMs) in the context of the Bulgarian education system, its student assessment framework, and the data collected and used by the education management information system.